Images Say More than Just Words: Effectiveness of Visual and Text Communication in Dispelling the Rent-Control Misconception - Jordi Brandts; Isabel Busom; Cristina Lopez-Mayan; Judith Panadés (Center for Economic Studies and ifo Institute (CESifo), 2023)
The highly popular belief that rent–control leads to an increase in the amount of affordable housing is in contradiction with ample empirical evidence and congruent theoretical explanations. It can therefore be qualified as a misconception. We present the results of a preregistered online experiment in which we study how to dispel this misconception using a refutational approach in two different formats, a video and a text. We find that the refutational video has a significantly higher positive impact on revising the misconception than a refutational text. This effect is driven by individuals who initially agreed with it and depart from it after the treatment. The refutational text, in turn, does not have a significant impact relative to a non–refutational text. Higher cognitive reflective ability is positively associated with revising beliefs in all interventions. Our research shows that visual communication effectively reduces the gap between scientific economic knowledge and the views of citizens.
Keywords: A10; A20; C90; D83; D90; 330; misconceptions; policy beliefs; communication; refutation; online experiments